Big Book: Attractive Media for Teaching Vocabulary to Lower Class of Young Learners: Big Book: Media Menarik untuk Mengajarkan Kosakata Kepada Anak Muda Kelas Bawah - Indrasari, Anissa; Novita, Dian; Megawati, Fika (JEES (Journal of English Educators Society), 2018)
Introducing English to young learners is challenging job. In order to make the students focus, something interesting should be brought inside the classroom. One of the media that can potentially entertain students as well as transfer the language concept is big book. The aim of this study is to find out whether there is significant effect in students’ vocabulary achievement in the first grade at primary school before and after being taught by using big book. In this case, the researcher used quantitative method with quasi experimental design. The subject of this research consisted of 35 students in each group. The main activities conducted in the learning process were try-out, pre-test, treatment and post-test. In analyzing, the researcher used ttest to calculate the data and to test the hypothesis. The result of this research revealed that the use of big book gives significant effect to students’ vocabulary achievement. Further, the result of vocabulary recognition task or VRT in I-B as experimental class showed more satisfying point. This implies that teachers for young learners have to be active and creative to present attractive media so that the learners can be motivated in learning the target language, especially in the context of EFL.